2019
DOI: 10.5114/fn.2019.88459
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ultrastructural findings in an ataxic variant of Kufor-Rakeb syndrome

Abstract: Introduction: Kufor-Rakeb syndrome (KRS) is a rare autosomal recessive neurodegenerative disorder manifesting as juvenile-onset atypical parkinsonism with pyramidal signs, supranuclear gaze palsy, dementia and characteristic minimyoclonus, with a notable phenotype variability. The responsible gene ATP13A2 was also associated with hereditary spastic paraplegia, uncomplicated early-or late-onset parkinsonism and a form of neuronal ceroid lipofuscinosis. We present clinical and ultrastructural findings in a 28-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…A postmortem histopathological study revealed lipofuscinosis with whorled lamellar deposits in neurons and the retina, cerebrum, and cerebellum glia. 47 The widespread neuronal and glial lipofuscin aggregation has suggested that this disease is similar to neuronal ceroid lipofuscinosis. 32 Loss of brain and retinal nerve cells is characteristic of neuronal ceroid lipofuscinoses, categorized as lysosomal storage diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A postmortem histopathological study revealed lipofuscinosis with whorled lamellar deposits in neurons and the retina, cerebrum, and cerebellum glia. 47 The widespread neuronal and glial lipofuscin aggregation has suggested that this disease is similar to neuronal ceroid lipofuscinosis. 32 Loss of brain and retinal nerve cells is characteristic of neuronal ceroid lipofuscinoses, categorized as lysosomal storage diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although further indocyanine green angiography (ICGA) is guided, studies for observation of vortex vein ampullae are needed to corroborate this hypothesis. A postmortem histopathological study revealed lipofuscinosis with whorled lamellar deposits in neurons and the retina, cerebrum, and cerebellum glia 47 . The widespread neuronal and glial lipofuscin aggregation has suggested that this disease is similar to neuronal ceroid lipofuscinosis 32 .…”
Section: Discussionmentioning
confidence: 99%
“…One salient aspect of our literature review is the combination of chorea and developmental delay. Indeed, several entities characterized by motor, language, [318][319][320] and action myoclonus [318][319][320][321][322][323] 606695 (PARK), 617225 (HSP) AR MxMD-MYORG-(PFBC) [324][325][326][327] 923…”
Section: Genetically Determined Choreamentioning
confidence: 99%
“…6 Cerebellar signs were very uncommon however action myoclonus, ataxia and seizures have been reported together with parkinsonism in a single Iranian family carrying ATP13A2 mutation. [7][8][9] More recently, a phenotype with lateonset ataxia and action myoclonus without parkinsonism has been reported. 10 We report a 47-year-old male presenting with late-onset myoclonic ataxia syndrome related to heterozygous variants in the ATP13A2 gene.…”
mentioning
confidence: 99%
“…According to published cases, this phenotype does not seem to be related to a specific type of mutation. [7][8][9][10] Author Roles…”
mentioning
confidence: 99%